Antibacterial activities of selected vegetables (Ulam) extracts / Noorshilawati Abdul Aziz ... [et al.] - Abdul Aziz, Noorshilawati; Abdullah, Nur Suraya; Mohammed, Anisah; Yusop, Mohamad Amir Shah (2011)
This research was carried out to study the antibacterial activity of ten species of Malay traditional vegetables against some species of bacteria that were pathogenic to human such as Escherichia coli, Pseudomonas aeruginosa, Salmonella typhimurium and Staphylococcus aureus, The ten species of table salads (ulam) used in this research were Averrhoa bilimbi L., Etlingera elatior, Vigna sinensis, Centella asiatica, Parkia speciosa, Diplazium esculentum, Manihot esculenta, Mentha arvensis L., Oenanthe javanica and Cosmos caudatus, The antibacterial activity was done by using disc diffusion method The result showed that all the sample extracts except Parkia speciosa inhibited the growth of Staphylococcus aureus and Salmonella typhimurium, For the Escherichia coli, only Averrhoa bilimbi L., Vigna sinensis, Centella asiatica and Diplazium esculentum inhibit the growth of these bacteria, In addition, all samples inhibit the growth of Pseudomonas aeruginosa except Parkia speciosa and Mentha arvensis L. Extracts of Etlingers elatior showed the highest antibacterial activity against Pseudomonas aeruginosa with 10,1 mm diameter of inhibition zone while Centella asiatica show the lowest antibacterial activity against Pseudomonas aeruginosa with 2.2 mm diameter of inhibition zone, Besides, the Etlingera elatior, Parkia speciosa, Manihot esculenta, Mentha arvensis L., Oenanthe javanica and Cosmos caudatus showed a negative result for the antibacterial test onto the gram-negative bacteria Escherichia coli.